2016
DOI: 10.1371/journal.pntd.0005181
|View full text |Cite
|
Sign up to set email alerts
|

Replication Protein A Presents Canonical Functions and Is Also Involved in the Differentiation Capacity of Trypanosoma cruzi

Abstract: Replication Protein A (RPA), the major single stranded DNA binding protein in eukaryotes, is composed of three subunits and is a fundamental player in DNA metabolism, participating in replication, transcription, repair, and the DNA damage response. In human pathogenic trypanosomatids, only limited studies have been performed on RPA-1 from Leishmania. Here, we performed in silico, in vitro and in vivo analysis of Trypanosoma cruzi RPA-1 and RPA-2 subunits. Although computational analysis suggests similarities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 47 publications
1
55
0
2
Order By: Relevance
“…We have previously shown that TcRPA‐1 interacts with ssDNA, while TcRPA‐2 does not bind ssDNA in an in vitro assay (Pavani et al. ). Since the termini of chromosomes expose the G‐overhang single‐stranded telomeric repeats, we first analyzed the abilities of TcRPA‐1 and TcRPA‐2 to bind the telomeric single‐stranded DNA.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that TcRPA‐1 interacts with ssDNA, while TcRPA‐2 does not bind ssDNA in an in vitro assay (Pavani et al. ). Since the termini of chromosomes expose the G‐overhang single‐stranded telomeric repeats, we first analyzed the abilities of TcRPA‐1 and TcRPA‐2 to bind the telomeric single‐stranded DNA.…”
Section: Resultsmentioning
confidence: 99%
“…Samples were incubated with mouse anti‐RPA‐1 antibody (Pavani et al. ) or with preimmune serum under agitation for 2 h at 4 °C. Samples were then harvested and transferred to a new tube containing 40 μl of protein G Sepharose beads (GE Healthcare Life Sciences, Amersham Place, U.K.) previously incubated with 5 mg/ml BSA for 2 h at 4 °C under agitation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations